Penerapan Teknologi Filter untuk Perbaikan Kuliatas Air Sungai Deket, Kabupaten Lamongan - Moh. Midchol Afan; Abdun Nafi Kurniawan; Yeni Anang Setiawan; Oky Dedy Wijaya; Miftahur Rohman (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2022)
The need for water, especially clean water, is currently increasing rapidly in line with the increase in population and the need for people to meet their needs such as drinking, cooking, washing, bathing, toilets and other activities. The high population growth has resulted in not all components of society being able to enjoy clean water. As a result, many of them use groundwater and river water where the quality of the water sources cannot be ascertained. This also applies to residents in the Deket District, Lamongan Regency. Therefore, community service activities are carried out by making water filtration technology sourced from the Deket River using the Slow Sand Filter method using up flow. The results of the filtration process analysis showed that the turbidity value decreased by 83.70%, hardness by 91.27%, pH reached 7.7, manganese by 82.47% and iron by 59.38%.